ALOGORITHMS FOR AUTOMATIC RUNWAY DETECTION ON VIDEO SEQUENCES - A. I. Logvin; A. V. Volkov (Научный вестник МГТУ ГА, 2016)
The article discusses algorithm for automatic runway detection on video sequences. The main stages of algorithm are represented. Some methods to increase reliability of recognition are described.